Perovskite and spinel composite microwave absorbing material and preparation method thereof

By using a structure of perovskite and spinel in the absorbing material, and using Sm0.5Sr0.5Mn1-xCoxO3 absorbing agent and MgAl2O4 wave transmissive agent with excellent oxidation resistance, the problem of poor absorbing properties of the absorbing material under high temperature conditions is solved, and the excellent absorbing performance and thermal expansion coefficient matching at high temperatures is achieved.

CN119874365APending Publication Date: 2025-04-25BEIHANG UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510094684.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing absorbing materials have poor absorption performance under high temperature conditions and the thermal expansion coefficient does not match the alloy, resulting in easy failure in high temperature environments.

Method used

A microwave absorbing material that is composited with perovskite and spinel is used, and a composite material with excellent antioxidant performance, with MgAl2O4 as the wave transmissive agent, is prepared by adjusting the proportion of the material and the treatment conditions.

Benefits of technology

Excellent wave absorption performance under high temperature conditions is achieved, and the stability and application potential of the material in high temperature environments are ensured by adjusting the thermal expansion coefficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874365A_ABST
    Figure CN119874365A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite and spinel composite microwave absorbing material and a preparation method thereof, the perovskite and spinel composite microwave absorbing material comprises the following raw materials by mass percentage: 45-60% of a wave absorbing agent and 40-55% of a wave transparent agent; the wave absorbing agent is Sm < 0.5 > Sr < 0.5 > Mn < 1-x > Co < x > O < 3 >, x is greater than or equal to 0.1 and less than or equal to 1, and Sm < 0.5 > Sr < 0.5 > Mn < 1-x > Co < x > O < 3 > is prepared by mixing a samarium source, a strontium source, a manganese source and a cobalt source and then carrying out ball milling and sintering treatment; mgAl2O4 is adopted as the wave-transparent agent. Mn is replaced by Co in the wave-absorbing agent, so that the wave-absorbing performance can be adjusted and improved; mgAl2O4 which is matched with alloy in thermal expansion performance, good in mechanical performance and low in dielectric constant is adopted as a wave-transparent agent, the composite material with the adjustable thermal expansion coefficient and the adjustable wave absorption crest position is prepared by adjusting the proportion, and the high-temperature application potential is achieved while the wave absorption performance is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of microwave absorbing materials, and in particular to a microwave absorbing material composited with perovskite and spinel and a preparation method thereof. Background Art

[0002] With the development of military science and technology, higher requirements are placed on the stealth performance of weapons and equipment. For example, during flight, the temperature of the missile tip, engine tail nozzle and other working parts may reach >900 ℃ or even higher. The Curie temperature of traditional magnetic materials is lower than 900 ℃. When used under high temperature conditions, they are prone to oxidation and magnetic loss, thus losing their absorbing effect; while conductive polymer absorbing materials have a short life in high temperature environments. Therefore, the selection of electrical loss and dielectric loss radar absorbing materials and the use of appropriate preparation technology to prepare high-performance high-temperature resistant absorbing coatings are the focus of current research in the field of absorbing coatings.

[0003] High-temperature absorbing materials usually add high-temperature resistant absorbers to glass or ceramic matrices, and optimize the electromagnetic properties of the materials by adjusting the content, morphology, size and distribution of the absorbers, so as to achieve better electromagnetic wave loss effects. The absorber is the key factor in determining high-temperature resistant absorbing materials. In addition to doping and modifying traditional absorbers to make them have better antioxidant and wave absorbing properties, scientific researchers are also committed to studying new absorbers with better antioxidant properties, such as MoSi2, TiB2 and other high-temperature compound absorbers. Although these materials have certain antioxidant capabilities below 600°C, when the ambient temperature of service exceeds 600°C, oxidation will occur, such as TiB2 oxidizing to TiO2, which is difficult to be used in high-temperature environments for a long time. Therefore, in order to face the harsh environment that is prone to oxidation at higher temperatures, the development of completely antioxidant and excellent performance absorbers is still one of the focuses of researchers.

[0004] The current research on absorbing materials mainly focuses on the modification and optimization of absorbents and the development of new materials. However, from the perspective of engineering applications, the selection of suitable carriers and wave-transmitting agents is also very critical. The temperature resistance of paraffin and resin is not as good as that of ceramic materials, and Al2O3 and SiO2 are mostly used as wave-transmitting agents in the literature reported so far. Although these two materials have good wave-transmitting performance, their thermal expansion coefficient is relatively low (SiO2 is 5×10 -6 K -1 , Al2O3 is 6×10 -6 K -1 ), the thermal expansion coefficient of nickel-based high-temperature alloys is usually between 10~15×10 -6 The thermal expansion coefficients of the two are quite different. According to literature reports, when the thermal expansion coefficients of the ceramic coating and the alloy are quite different, the thermal stress generated between the two during service is relatively large, and it is easy to fail during application. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a microwave absorbing material composite of perovskite and spinel and a preparation method thereof, and solve the technical problem that the high-temperature absorbing performance of the absorbing material in the prior art is poor.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a microwave absorbing material composited with perovskite and spinel, wherein the raw materials include 45-60% of a microwave absorbing agent and 40-55% of a microwave transmitting agent by mass percentage; the microwave absorbing agent is Sm 0.5 Sr 0.5 Mn 1-x Co x O3, 0.1≤x≤1, Sm 0.5 Sr 0.5 Mn 1-x Co x O3 is prepared by mixing samarium source, strontium source, manganese source and cobalt source and then subjecting them to ball milling and sintering treatment; the wave-transmitting agent is MgAl2O4.

[0007] In a second aspect, the present invention provides a method for preparing a microwave absorbing material composited with perovskite and spinel, comprising the following steps: S1, weighing and mixing samarium source, strontium source, manganese source and cobalt source according to a stoichiometric ratio, mixing, ball milling, drying, sieving and sintering to obtain Sm 0.5 Sr 0.5 Mn 1-x Co x O3; S2, Sm 0.5 Sr 0.5 Mn 1-x Co x O3 and MgAl2O4 are mixed evenly in proportion to obtain a mixed powder; S3, a binder is added to the mixed powder, and after mixing evenly, a green body is obtained by cold pressing; the green body is sintered to obtain a microwave absorbing material composite of perovskite and spinel.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention adopts Sm 0.5 Sr 0.5 Mn 1-x Co xO3 is used as a wave absorber, in which Co replaces Mn, which effectively regulates the polarization ability of the wave absorber, and then regulates the electromagnetic parameters of the material to adjust the wave absorbing performance. At the same time, the substitution of Co can appropriately reduce the dielectric constant of the composite material, which is beneficial to improving the wave absorbing performance. MgAl2O4, which has thermal expansion properties matching the alloy, good mechanical properties and low dielectric constant, is used as a wave penetrating agent, and by adjusting the ratio of perovskite phase and spinel phase, the wave absorbing performance and thermal expansion coefficient are changed to prepare a composite material with adjustable thermal expansion coefficient and adjustable absorption peak position, which has the potential for high-temperature application while ensuring the wave absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is the dielectric constant of Comparative Example 1 of the present invention; Figure 2 is the reflection loss curve of comparative example 1 of the present invention; Figure 3 is the impedance matching factor of Comparative Example 1 of the present invention; Figure 4 is the attenuation factor of Comparative Example 1 of the present invention; Figure 5 is the thermal expansion coefficient curve of comparative example 1 of the present invention; Figure 6 is the dielectric constant of Example 1 of the present invention; Figure 7 is a reflection loss curve of Example 1 of the present invention; Figure 8 is the impedance matching factor of embodiment 1 of the present invention; Fig. 9 is the attenuation factor of Example 1 of the present invention; Fig.10 is the thermal expansion coefficient curve of Example 1 of the present invention; Fig.11 is the dielectric constant of Example 2 of the present invention; Fig.12 is a reflection loss curve of Example 2 of the present invention; Fig.13 is the impedance matching factor of embodiment 2 of the present invention; Fig.14 is the attenuation factor of embodiment 2 of the present invention; Fig.15 is a thermal expansion coefficient curve of Example 2 of the present invention; Fig.16 is the dielectric constant of Comparative Example 2 of the present invention; Fig.17 is the reflection loss curve of comparative example 2 of the present invention; Fig.18 is the impedance matching factor of Comparative Example 2 of the present invention; Fig.19is the attenuation factor of Comparative Example 2 of the present invention; Fig. 20 It is the thermal expansion coefficient curve of comparative example 2 of the present invention. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] Although magnetic absorbers and some carbide and boride absorbers have certain absorbing properties, their antioxidant properties are very poor and are not suitable for use under high temperature conditions. The present invention uses oxide perovskite with excellent antioxidant properties as the absorber, and uses MgAl2O4 with thermal expansion properties matching the alloy, good mechanical properties, and low dielectric constant as the wave-transmitting agent. The composite microwave absorbing material has excellent high-temperature absorbing properties and a controllable thermal expansion coefficient.

[0012] In a first aspect, the present invention provides a microwave absorbing material composited with perovskite and spinel, wherein the raw materials include 45-60% of a microwave absorbing agent and 40-55% of a microwave transmitting agent by mass percentage; the microwave absorbing agent is Sm 0.5 Sr 0.5 Mn 1-x Co x O3, 0.1≤x≤1, Sm 0.5 Sr 0.5 Mn 1-x Co x O3 is prepared by mixing samarium source, strontium source, manganese source and cobalt source and then subjecting them to ball milling and sintering treatment; the wave-transmitting agent is MgAl2O4.

[0013] It is understood that the amount of the wave absorbing agent includes but is not limited to 45%, 48%, 50%, 52%, 55%, 58% or 60%; the amount of the wave transmitting agent includes but is not limited to 40%, 42%, 45%, 48%, 50%, 52% or 55%; Sm 0.5 Sr 0.5 Mn 1-x Co x The value of x in O3 includes but is not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0.

[0014] In a second aspect, the present invention provides a method for preparing a microwave absorbing material composite of perovskite and spinel, comprising the following steps: S1, weighing and mixing samarium source, strontium source, manganese source and cobalt source according to the stoichiometric ratio, mixing, ball milling, drying, sieving and sintering to obtain Sm 0.5 Sr0.5 Mn 1-x Co x O3; S2, Sm 0.5 Sr 0.5 Mn 1-x Co x O3 and MgAl2O4 are mixed evenly in proportion to obtain a mixed powder; S3, adding a binder to the mixed powder, mixing evenly and then cold pressing to obtain a green body; the green body is sintered to obtain a microwave absorbing material composite of perovskite and spinel.

[0015] Preferably, in step S1, the samarium source is Sm2O3; the strontium source is SrCO3 or SrO; the manganese source is MnO2, MnCO3 or Mn3O4; and the cobalt source is Co3O4 or Co2O3.

[0016] Preferably, in step S1, the ball milling conditions include: the mass ratio of raw materials, grinding balls and alcohol solvent is 1: (1.8-2.2): (0.8-2.2), the ball milling speed is 300-500 r / min, and the ball milling time is 10-14h.

[0017] Preferably, in step S1, drying is performed at 75-85° C.; and sieving is performed by grinding and then passing through a 200-mesh sieve.

[0018] Preferably, in step S1, the sintering process is performed at 1100-1200° C. for 4-6 hours.

[0019] Preferably, in step S2, the mixed powder is Sm 0.5 Sr 0.5 Mn 1-x Co x O3 and MgAl2O4 are mixed in proportion, ball-milled, dried and sieved to obtain the product.

[0020] Preferably, in step S3, the binder comprises a PVA aqueous solution with a mass concentration of 4 to 6%; the amount of the binder used is 1 to 5 wt % of the total mass of the binder and the mixed powder.

[0021] Preferably, in step S3, the cold press molding pressure is 10-20 MPa, and the holding time is 4-6 min.

[0022] Preferably, in step S3, the sintering treatment is performed at 1450-1550° C. for 4-6 hours.

[0023] The main mechanism of action and advantages of the present invention: (1) The present invention effectively regulates the polarization ability of the absorber by changing the doping ratio in the absorber and replacing Mn with Co, thereby regulating the electromagnetic parameters of the material to adjust the absorbing performance. At the same time, the substitution of Co can appropriately reduce the dielectric constant of the composite material, which is beneficial to improving the absorbing performance; (2) The present invention uses MgAl2O4 material as the wave-transmitting material, which has a low dielectric constant, thermal expansion properties that match the alloy, and good mechanical properties, and is suitable as a carrier in the composite material; (3) The present invention adjusts the ratio of the perovskite phase and the spinel phase to change the absorbing performance and the thermal expansion coefficient, thereby preparing a composite material with an adjustable thermal expansion coefficient and an adjustable absorbing peak position. While ensuring the absorbing performance, it has the potential for high-temperature application.

[0024] The present invention is further described in detail below through specific examples.

[0025] Comparative Example 1 S1, Sm2O3, SrCO3 and MnO2 were prepared in a molar ratio of 1:2:4: 70.01 g of Sm2O3, 60 g of SrCO3 and 70 g of MnO2 were weighed respectively, a total of 200 g was put into a ball mill, and anhydrous ethanol was used as a solvent for ball milling, wherein the raw materials, grinding balls and anhydrous ethanol were weighed in a mass ratio of 1:2:2, and the slurry was formed at a speed of 400 r / min for 12 h; the obtained slurry was dried in a drying oven at 80 °C and ground through a 200 mesh sieve; the sieved powder was sintered at 1150 °C for 5 h, and the obtained powder was ground through a 200 mesh sieve to obtain Sm 0.5 Sr 0.5 MnO3 powder.

[0026] S2, the absorbing powder Sm 0.5 Sr 0.5 MnO3 and MgAl2O4 were weighed in a mass percentage ratio of 60wt%:40wt%. The weighed powders were then mixed and weighed with grinding balls and anhydrous ethanol in a mass ratio of 1:2:2, and then ball milled at a speed of 400r / min for 12h. The obtained slurry was dried at 80°C and passed through a 200-mesh sieve to obtain a mixed powder.

[0027] S3, weigh a certain amount of 12 g of the mixed powder in step S2, add 5wt% PVA aqueous solution as a binder, and the amount of binder added is 5wt% of the total mass of the binder and the mixed powder. After mixing evenly, cold pressing is used to obtain a green body, and the pressure during cold pressing is 15 MPa and the holding time is 5 min. The green body is sintered in a high-temperature sintering furnace, and the sintering system is 1500℃ / 5 h to obtain a composite microwave absorbing material.

[0028] Example 1 The only difference from Comparative Example 1 is that part of Co is added in step S1 to replace part of Mn, and the other steps and conditions are the same as those in Comparative Example 1 to obtain Sm 0.5 Sr 0.5 Co 0.3 Mn 0.7 O3 powder.

[0029] The specific difference is that the molar ratio of Sm2O3, SrCO3 and MnO2, Co3O4 oxides is 1:2:1.4:0.2. That is, 0.3 mol of Co is doped 3+ , the absorber is composed of Sm 0.5 Sr 0.5 MnO3 turns into Sm 0.5 Sr 0.5 Co 0.3 Mn 0.7 Specifically, 60.32 g of SrCO3, 49.73 g of MnO2, 19.5 g of Co3O4 and 70.45 g of Sm2O3 were weighed, a total of 200 g.

[0030] Example 2 The only difference from Example 1 is that Sm is changed 0.5 Sr 0.5 Co 0.3 Mn 0.7 The ratio of O3 and MgAl2O4 phases was adjusted to 50wt%:50wt%, and the other steps and conditions were the same as in Example 1.

[0031] Comparative Example 2 The only difference from Example 1 is that Sm is changed 0.5 Sr 0.5 Co 0.3 Mn 0.7 The ratio of O3 and MgAl2O4 phases was adjusted to 40wt%:60wt%, and the other steps and conditions were the same as in Example 1.

[0032] Performance Testing The microwave absorption performance of the materials obtained in the above embodiments and comparative examples was tested using the standard GB / T 35679-2017 (wherein the reflection loss value was derived from the transmission line theory after testing the dielectric constant); the thermal expansion coefficient of the obtained materials was tested using the standard GB / T16535-2008; and the results of the article "Dual Properties of Microwave Absorption and Thermal Protection in La 0.5 Sr 0.5FeO3–Al2O3PseudobinaryComposites” as the reference group; the specific test results are as follows Figure 1-Figure 20 And as shown in Table 1 below.

[0033] The testing principle of thermal expansion coefficient is: monitor the expansion rate of the sample during temperature change through a precision displacement sensor ( dL / L 0), and calculate the thermal expansion coefficient at different temperatures according to the expansion rate at different temperatures ( TEC ), the specific calculation formula is:

[0034] In the formula T 1 and T ref In this paper, the test temperature range is from room temperature to 1000 ℃, and the reference temperature is uniformly set to room temperature (25 ℃).

[0035] Table 1 Test results of material properties obtained in Examples and Comparative Examples

[0036] Note: The impedance matching factor varies with the absorption frequency. The impedance matching factor data corresponding to the maximum absorption frequency at a sample thickness of 2.5 mm is taken in the present invention. The thermal expansion coefficient value selected in the present invention is the corresponding thermal expansion coefficient value selected at 1000°C.

[0037] As shown in Table 1, the reference group combines Al2O3 with LSF type absorber. Under similar proportions, its thermal expansion coefficient is only 8.9×10 -6 K -1 The thermal expansion coefficient of the material of the present invention is greater than that of the material.

[0038] Depend on Figure 1-Figure 5 It can be seen that the MgAl2O4 material used in the present invention is a material with a low dielectric constant and a suitable thermal expansion coefficient. Combining it with the synthesized absorber can prepare a material with a thermal expansion coefficient matching that of the alloy. Among them, the thermal expansion coefficient of the material in Comparative Example 1 reaches 10.2×10 -6 K -1 (like Figure 5 As shown); however, the material has poor wave absorption performance, with the peak absorption peak at -3.5 dB. This is because the material has poor impedance matching performance, with the impedance matching factor reaching more than 60 (the smaller the impedance matching factor, the better). Therefore, Co doping and absorber content were regulated in an attempt to change the dielectric constant to regulate impedance matching performance.

[0039] Depend on Figure 6-Figure 10It can be seen that in Example 1, by changing the doping ratio of Co, the dielectric constant (such as Figure 1 and Figure 6 The impedance matching performance is improved and the reflection loss capability is increased. The absorption bandwidth of <-5 dB at 1.5 mm is 3 GHz. The thermal expansion coefficient is 10.5×10 -6 K -1 .

[0040] Relative to Example 1, Example 2 and Comparative Example 2 adjusted the ratio of the two phases, such as Figure 11-Figure 20 As shown, the position and intensity of the absorption peak can be adjusted. In Example 2, when the thickness of the material is 2.3 mm, the peak value of the reflection loss reaches -65 dB. The thermal expansion coefficient is 9.5×10 -6 K -1 Compared with Example 1, Example 2 reduces Sm 0.5 Sr 0.5 Co 0.3 Mn 0.7 The ratio of O3 phase is improved, and the wave absorption performance of the material is improved. From the dielectric constant diagram in Example 2 ( Fig.11 ) and impedance matching factor diagram ( Fig.13 ) It can be seen that reducing the proportion of the absorber reduces the dielectric constant and the impedance matching factor. The smaller the impedance matching factor, the more electromagnetic waves can enter the material without being reflected back, thereby improving the absorbing performance.

[0041] In contrast, the content of the absorber was further reduced in Comparative Example 2. The absorbing performance decreased and the reflection loss value became -4.5 dB. This is because the attenuation factor was smaller than that in Example 2. The smaller attenuation factor made the material have poor attenuation ability for electromagnetic waves. The reflection loss value was only -4.5 dB, which led to the deterioration of the absorbing performance. The thermal expansion coefficient was 9.3×10 -6 K -1 .

[0042] Therefore, after comprehensive consideration, the absorber doped with Co at a concentration of 0.3 and composited with 50wt% MgAl2O4 has the best performance.

[0043] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A microwave absorbing material composite of perovskite and spinel, characterized in that: In terms of mass percentage, the raw materials include 45-60% of wave absorbing agent and 40-55% of wave transmitting agent; The absorbent is Sm 0.5 Sr 0.5 Mn 1-x Co x O3, 0.1≤x≤1, Sm 0.5 Sr 0.5 Mn 1-x Co x O3 is prepared by mixing samarium source, strontium source, manganese source and cobalt source, and then ball milling and sintering. The wave-transmitting agent is MgAl2O4.

2. The method for preparing the microwave absorbing material of perovskite and spinel composite according to claim 1, characterized in that: The following steps are involved: S1, weighing and mixing samarium source, strontium source, manganese source and cobalt source according to the stoichiometric ratio, mixing, ball milling, drying, sieving and sintering to obtain Sm 0.5 Sr 0.5 Mn 1-x Co x O3; S2, Sm 0.5 Sr 0.5 Mn 1-x Co x O3 and MgAl2O4 are mixed uniformly in proportion to obtain a mixed powder; S3, adding a binder to the mixed powder, mixing evenly and then cold pressing to obtain a green body; the green body is sintered to obtain a microwave absorbing material composite of perovskite and spinel.

3. The method for preparing the microwave absorbing material of perovskite and spinel composite according to claim 2, characterized in that: In step S1, the samarium source is Sm2O3; the strontium source is SrCO3 or SrO; the manganese source is MnO2, MnCO3 or Mn3O4; and the cobalt source is Co3O4 or Co2O3.

4. The method for preparing the microwave absorbing material of perovskite and spinel composite according to claim 2, characterized in that: In step S1, the ball milling conditions include: the mass ratio of raw materials, grinding balls and alcohol solvent is 1: (1.8-2.2): (0.8-2.2), the ball milling speed is 300-500 r / min, and the ball milling time is 10-14h.

5. The method for preparing the microwave absorbing material composite of perovskite and spinel according to claim 2, characterized in that: In step S1, the drying is performed at 75-85°C; and the screening is performed by passing through a 200-mesh sieve after grinding.

6. The method for preparing the microwave absorbing material composite of perovskite and spinel according to claim 2, characterized in that: In step S1, the sintering process is performed at 1100-1200° C. for 4-6 hours.

7. The method for preparing the microwave absorbing material of perovskite and spinel composite according to claim 2, characterized in that: In step S2, the mixed powder is Sm 0.5 Sr 0.5 Mn 1-x Co x O3 and MgAl2O4 are mixed in proportion, ball-milled, dried and sieved to obtain the product.

8. The method for preparing the microwave absorbing material of perovskite and spinel composite according to claim 2, characterized in that: In step S3, the binder includes a PVA aqueous solution with a mass concentration of 4 to 6%; the amount of the binder used is 1 to 5% of the total mass of the binder and the mixed powder.

9. The method for preparing the microwave absorbing material composite of perovskite and spinel according to claim 2, characterized in that: In step S3, the cold pressing pressure is 10-20 MPa, and the holding time is 4-6 min.

10. The method for preparing the microwave absorbing material of perovskite and spinel composite according to claim 2, characterized in that: In step S3, the sintering treatment is performed at 1450-1550° C. for 4-6 hours.

Citation Information

Patent Citations

  • Rare earth modified mesoporous spinel type ferrite wave-absorbing material and preparation method thereof

    CN116443944A

  • Preparation method of high-temperature radar wave-absorbing coating, coating and stealth component

    CN118441233A

  • Heat-proof and stealth dual-function coating material capable of being formed by coating and preparation method of heat-proof and stealth dual-function coating material

    CN118599346A